Buffalo oocyte‐secreted factors promote cumulus cells apoptosis and the rate of cGMP production but not steroidogenesis. (22nd October 2018) - Moussa, Mahmoud; Li, Meng‐Qi; Zheng, Hai‐Ying; Yang, Chun‐Yan; Yan, Sheng‐Fei; Yu, Nong‐Qi; Huang, Jia‐Xiang; Shang, Jiang‐Hua
Contents: The objectives of this study were to investigate the effect of buffalo oocyte‐secreted factors (OSFs) on cumulus cells (CCs) functions, apoptosis and cGMP generation, and whether the direct contact between oocyte and CCs is essential for oocyte‐mediated regulation of CCs functions. Buffalo CCs were cultured during IVM within three groups: (a) intact cumulus–oocyte complexes (COCs), (b) CCs cocultured with denuded oocytes (DOs) (CCs + DOs) and (c) CCs monolayer cultured alone (CCsM). After 24 hr of IVM, CCs were harvested for evaluation of the relative mRNA abundance of the genes encoding gap junction (GJA1), glycolysis (PFKP and LDHA), apoptosis (CASPASE‐3 and BCL‐2) and steroidogenesis (ER‐β and PGR) by QRT‐PCR, and CASPASE‐3 proteins, using western blot. Intracellular cGMP content was also assessed by ELISA. Results showed that the relative abundance of LDHA, PFKP and BCL‐2 significantly increased ( p < 0.05) in COCs, whereas GJA1 and CASPASE‐3 exhibited lower expression ( p < 0.05) compared to CCs + DOs and CCsM groups. However, the expression levels of CASPASE‐3, both mRNA and protein, were significantly ( p < 0.05) downregulated in CCs + DOs compared to CCsM. There was no significant difference in the expression level of PGR and ER‐β between the groups. The intracellular content of cGMP was notably ( p < 0.05) higher in COCs compared to CCs + DOs and CCsM groups. In conclusion, this study demonstrated, for the first time, that buffalo OSFs protect CCs against apoptosis and stimulate their cGMP production; however, the regulation of cumulus glycolysis and gap junction is confined to those in close contact with the oocyte. Neither OSFs from COCs nor those from DOs have any effect on CCs steroidogenesis.